The Effect of Ball-Specific Exercises on Developing Maximum Anaerobic Capacity and Moderate Performance Endurance in Young Football Players (Texas Journal of Multidisciplinary Studies, 2024)
To investigate the effect of ball-specific exercises on maximum anaerobic capacity and moderate performance endurance among young football players. Research Methodology: - The researcher employed an experimental design, using a pretest-posttest design with control and experimental groups, suitable for the nature and problem of the research. Recommendations: - It is essential to use high-intensity interval training when implementing ball-specific exercises, given its significant role in enhancing performance levels. - Relying on ball-specific exercises can foster enjoyment and motivation during training, which may lead to improved application of exercises and consequently positively impact the players' physical and technical performance.